(untitled) (Mwanga wa Lugha, 2018)
Shetani Msalabani is the Kiswahili translated version of Ngugi wa Thiong’o’s novel Devil on the Cross, which was originally written in Gikuyu as Caitaani Mutharaba-ini. It was translated from English into Kiswahili by Clement Kabugi. It explores the extent and effects of neo-colonialism in independent Kenya as manifested in the political, economic and socio-cultural domains. The aim of this paper is to discuss the challenges of translating the novel from English into Kiswahili and to examine the strategies used by the translator to deal with them. The paper focuses on the challenges arising from the influence of the source language and its culture, the target language and its culture, the author’s ideology and problems of the genre (novel) itself and how these affect the quality of translation. The paper evaluates the success of the translator in conveying the message and is guided by the principles of a Linguistic Theory of Translation as explained by Catford (1965).